Covid-19 and In(di)genuity: Lessons from Indigenous resilience, adaptation, and innovation in times of crisis - Brant-Birioukov, Kiera (Prospects (Paris), 2021)
In the midst of the global Covid-19 pandemic, educators are invited to pause and reconsider the legacies this crisis will leave for future generations. What lessons do we take forward in a post-Covid-19 curriculum? This article contemplates the value of Indigenous resilience, innovation, and adaptation in times of crisis—“In(di)genuity”, if you will—and considers its implications on Indigenous knowledge and the curricular discourse more broadly. Despite encouraging developments in Indigenous education since the Truth and Reconciliation Commission, a settler historical consciousness continues to pervade the modern discourse of Indigenous education, insofar as Indigenous knowledge is often perceived as outdated, irrelevant, or inferior to Western knowledge systems. This problematic misconception ignores the resilience, innovation, and adaptation that Indigenous peoples have demonstrated in the face of historical crises. This article offers an Indigenous perspective on crisis, grief, and renewal in the context of Covid-19 and advocates for the renewal of the Canadian curricular landscape.